2014
DOI: 10.1038/ncb2953
|View full text |Cite
|
Sign up to set email alerts
|

An integrin β3–KRAS–RalB complex drives tumour stemness and resistance to EGFR inhibition

Abstract: Tumor cells, with stem-like properties, are highly aggressive and often display drug resistance. Here, we reveal that integrin αvβ3 serves as a marker of breast, lung, and pancreatic carcinomas with stem-like properties that are highly resistant to receptor tyrosine kinase inhibitors such as erlotinib. This was observed in vitro and in mice bearing patient-derived tumor xenografts or in clinical specimens from lung cancer patients that had progressed on erlotinib. Mechanistically, αvβ3, in the unligated state,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
340
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 330 publications
(362 citation statements)
references
References 58 publications
14
340
0
8
Order By: Relevance
“…Integrin a v b 3 -expressing tumor-initiating cells from breast, lung, and pancreatic carcinomas are resistant to EGFR inhibitors [53]. NF-kB activation contributes to this phenotype because integrin a v b 3 drives tumor stemness and resistance to EGFR inhibitors by interacting with Kirsten rat sarcoma viral oncogene homolog GTPase (KRAS) through galectin-3 to promote the sequential activation of both GTPase v-Ral simian leukemia oncogene homolog B GTPase (RALB) and TANK-binding kinase-1 (TBK1), which then targets c-Rel, a NF-kB protein [53]. Interestingly, this pathway does not require the binding of any ligand to integrin a v b 3 , demonstrating that resistance to EGFR inhibitors can be cell autonomous.…”
Section: Reviewmentioning
confidence: 99%
“…Integrin a v b 3 -expressing tumor-initiating cells from breast, lung, and pancreatic carcinomas are resistant to EGFR inhibitors [53]. NF-kB activation contributes to this phenotype because integrin a v b 3 drives tumor stemness and resistance to EGFR inhibitors by interacting with Kirsten rat sarcoma viral oncogene homolog GTPase (KRAS) through galectin-3 to promote the sequential activation of both GTPase v-Ral simian leukemia oncogene homolog B GTPase (RALB) and TANK-binding kinase-1 (TBK1), which then targets c-Rel, a NF-kB protein [53]. Interestingly, this pathway does not require the binding of any ligand to integrin a v b 3 , demonstrating that resistance to EGFR inhibitors can be cell autonomous.…”
Section: Reviewmentioning
confidence: 99%
“…While it is speculated that single targeted therapies may not be enough to surmount the dynamic nature and adaptive capacity of tumor cells [57], rational combinatorial therapies have the potential to overcome these resistance mechanisms with additional advantages such as blocking multiple survival pathways. It was recently found that as drug resistance occurs, tumor cells acquire stem cell-like properties giving them the capacity to survive throughout the body and essentially ignore the drugs [58]. In a study on acquisition of resistance against tyrosine kinase inhibitors (TKIs), the molecular pathway that facilitates pluripotency of tumor cells and drug resistance was delineated, and existing drugs that exploit this pathway (e.g., bortezomid) were identified.…”
Section: Challenge: Drug Resistance and The Role Of Tumor Genetic DIVmentioning
confidence: 99%
“…Specifically, we found that while GPBAR1 activation reduced the expression of MMP7 and MMP13 genes, the expression of two other metalloproteinases MMP3 and MMP10 was robustly enhanced by all there agonists [31][32][33]. Further on, all three GPBAR1 ligands were effective in inducing the expression of ITGB3 [34], a integrin beta-chain subunit coded by a serotoninrelated gene on chromosome 17, that has been reported to be associated with the risk of several human cancers, including colorectal cancer. The ITGB3 family includes αIIb β3 and αvβ3.…”
Section: Discussionmentioning
confidence: 70%